2016
DOI: 10.5194/acp-16-9273-2016
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of mixing in liquid clouds – Part 3: Inhomogeneous mixing

Abstract: Abstract. An idealized diffusion-evaporation model of timedependent mixing between a cloud volume and a dropletfree volume is analyzed. The initial droplet size distribution (DSD) in the cloud volume is assumed to be monodisperse. It is shown that evolution of the microphysical variables and the final equilibrium state are unambiguously determined by two non-dimensional parameters. The first one is the potential evaporation parameter R, proportional to the ratio of the saturation deficit to the liquid water co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Isobaric mixing of two nearly saturated volumes with T 1 = T 2 may result in supersaturated environment (e.g., Rogers, 1976;Bohren and Albrecht, 1998). Mixing resulting in supersaturation is different in principle from the mixing with evaporating droplets.…”
Section: Effect Of Temperature Case T 1 = Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Isobaric mixing of two nearly saturated volumes with T 1 = T 2 may result in supersaturated environment (e.g., Rogers, 1976;Bohren and Albrecht, 1998). Mixing resulting in supersaturation is different in principle from the mixing with evaporating droplets.…”
Section: Effect Of Temperature Case T 1 = Tmentioning
confidence: 99%
“…The evaporation time required to reach equilibrium during homogeneous mixing is discussed in detail in Pinsky et al (2016b), and it is usually limited by a few tens of seconds. However, progressive mixing is not limited in time.…”
Section: Expected Relationships Between the Momentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second timescale characterizes rate of droplet evaporation and corresponding changes of supersaturation. In this study, as well as later in study by Pinsky et al (2016) (hereafter, Part 3), it will be shown that the characteristic evaporation time is the phase relaxation time τ pr , which determines the rate of change of supersaturation during condensation or evaporation (Mazin, 1968;Korolev and Mazin, 2003) …”
Section: Introductionmentioning
confidence: 99%
“…However, C r and the directly related relative dispersion 20 are important for models as the relative dispersion defines the effective rate of mixing of a puff and therefore the decay rate of concentration fluctuations (e.g. Sawford, 2004;Cassiani et al, 2005;Pinsky et al, 2016;Marro et al, 2018).…”
mentioning
confidence: 99%